Agrifood systems in low- and middle-income countries: Status and opportunities for smallholder dairy in LMIC - Domínguez Salas, Paula; Omore, Amos O.; Omosa, Esther B.; Ouma, Emily A. (Elsevier, 2019)
Milk is among the most researched animal products, counting more evidence available than any other animal-source food. Yet important challenges and knowledge gaps still exist; it presents nevertheless a wealth of opportunities to leverage nutrition, quite often context-specific. This chapter covers the contribution of milk to nutrition and health, as well as the potential for expansion of milk in low- and middle-income countries, the barriers and enablers to such expansion, and surrounding issues related to sustainability and trade-offs.